ANALISIS KAJIAN FEMINISME TERHADAP TOKOH PEREMPUAN DALAM NOVEL PEREMPUAN DI TITIK NOL KARYA NAWAL EL- SAADAWI DALAM MODEL ANALISIS WACANA KRITIS PADA TEORI NORMAN FAIRCLOUGH - Juni Yanti; Karimaliana Karimaliana (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the representation of female characters in the novel Woman at Point Zero by Nawal El-Saadawi through a feminist perspective using Norman Fairclough’s Critical Discourse Analysis model. The focus of this research lies in how forms of gender injustice, power relations, and the resistance of female characters are represented in the novel’s text. This research employed a descriptive qualitative method with a critical discourse analysis approach covering three dimensions, namely text analysis, discursive practice, and socio-cultural practice. The results of the study indicate that the main female character in the novel experiences various forms of oppression, such as subordination, physical and sexual violence, exploitation, and marginalization influenced by patriarchal culture. In the text dimension, the study found the use of diction, dialogues, and narratives that portray male domination over women. In the discursive practice dimension, the novel represents social criticism toward societal constructions that place women in unequal positions. Meanwhile, in the socio-cultural practice dimension, the novel illustrates how patriarchal systems and social power shape gender inequality in women’s lives. The female character in the novel is also portrayed as a figure who resists the hegemony and oppression she experiences.